Assessing Bioavailability of DDT and Metabolites in Marine Sediments using Solid-Phase Microextraction with Performance Reference Compounds - Bao, Lian-Jun (2013)
Solid-phase microextraction (SPME) has often been used to estimate the freely dissolved concentration (C(free)) of organic contaminants in sediments. A significant limitation in the application of SPME for C(free) measurement is the requirement for attaining equilibrium partition, which is often difficult for strongly hydrophobic compounds such as DDT. A method was developed using SPME with stable isotope-labeled analogues as performance reference compounds (PRCs) to measure C(free) of DDT and metabolites (DDTs) in marine sediments. Six (13)C-labeled or deuterated PRCs were impregnated into polydimethylsiloxane (PDMS) fiber before use. Desorption of PRCs from PDMS fibers and absorption of DDTs from sediment were isotropic in a range of sediments evaluated ex situ under well-mixed conditions. When applied to a historically contaminated marine sediment from a Superfund site, the PRC-SPME method yielded C(free) values identical to those found by using a conventional equilibrium SPME approach (Eq-SPME), wherease the time for mixing was reduced from 9 d to only 9 h. The PRC-SPME method was further evaluated against bioaccumulation of DDTs by Neanthes arenaceodentata in the contaminated sediment with or without amendment of activated carbon or sand. Strong correlations were consistently found between the derived equilibrium concentrations on the fiber and lipid-normalized tissue residues for DDTs in the worms. Results from the present study clearly demonstrated the feasibility of coupling PRCs with SPME sampling to greatly shorten sampling time, thus affording much improved flexibility in the use of SPME for bioavailability evaluation. Environ Toxicol Chem 2013;32:1946–1953.